Aktivitas Antibakteri Fraksi Etil Asetat Kulit Buah Manggis (Garcinia mangostana L.) Terhadap Staphylococcus aureus - Halid, Musparlin; M.Si, Hardani (Pharmaceutical and Traditional Medicine, 2022)
Some of the bacteria that cause infection include Shigella flexneri, Pseudomonas aeruginosa, Escherichia coli and Staphylococcus aureus. Staphylococcus aureus is a type of gram-positive bacteria that often causes disease in humans. Infection by bacteria that causes disease with characteristic signs of inflammation, necrosis, and abscess formation. This study aims to determine the antibacterial activity of the ethyl acetate fraction of mangosteen rind (Garcinia mangostana L.) against Staphylococcus aureus. In this study using experimental research methods were carried out to prove the hypothesis. Experimental research is research by conducting experimental activities that aim to determine the symptoms or effects that arise as a result of certain treatments on the antibacterial activity test of the ethyl acetate fraction of mangosteen rind (Garcinia mangostana L.) against Staphylococcus aureus. The population in this study was the mangosteen fruit. And the sample used in this study was mangosteen rind. While the research instrument uses the results of laboratory tests. The results of the antibacterial activity test of the ethyl acetate fraction of mangosteen rind (Garcinia mangostana L.) against Staphylococcus aureus. Results Based on research that has been done that the ethyl acetate fraction of mangosteen rind extract (Garcinia mangostana L.) has antibacterial activity against Staphylococcus aureus. With the most effective concentration at a concentration of 25%. at concentrations of 50%, 75% and 100% the same has a moderate concentration from the range of 7.95-10.77 mm so that all concentrations tested belong to the category of moderate antibacterial activity.